Characteristics and reasons for the discharge interruption of the Iskrets karst spring (Western Balkans, Bulgaria) - Benderev, Al. (Acta carsologica, 2025)
The Iskrets spring is one of the most significant karst springs in Bulgaria. ? specific feature of this spring are irregular and abrupt reductions of its discharge after some earthquakes as well as other reasons related to the recharge. This study aims to present a reasonable hypothesis for the reasons of the discharge interruptions. A main feature of the Iskrets karst system is the fact that it is dominated by unconfined water flow in the unsaturated zone with velocities varying in a wide range. This creates conditions for significant erosion, transport and redeposition of the fluvial cave sediments. As a result, in the zones where there is a sharp decrease in the water velocity, a considerable accumulation of sediments occurs which can even fill the entire section of the passage-way and leads to a temporary blocking of the spring discharge. It is supposed that an appropriate section where this happens is located near to the discharge point of the spring. Most likely the main reason for the cave deposit dis-placement is the soil liquefaction caused by the seismic impact. It has been found that the duration of the discharge interrup-tion period is longer at low water flow rates.
Keywords: aquatic resources; Bolgarija; Bulgaria; cave sediments; jamski sedimenti; karst (geology); karst springs; kras (geologija); kraški izviri; vodni viri